HUBUNGAN STATUS GIZI IBU HAMIL DENGAN KEJADIAN BAYI LAHIR MATI DI KABUPATEN BANJARPERIODE 2011-2012 - Mariyatul, Mariyatul; Triawanti, Triawanti; Noor, Meitria Syahadatina (Universitas Lambung Mangkurat, 2014)
Stillbirth is the birth of the conception product of dead who have reached 28 weeks of gestational age (body weight ≥ 1000 grams). Stillbirth could be influenced by nutritional status of maternal pregnant. The aim of research is to indicate relationship nutritional status of maternal pregnant with stillbirth incident in Banjar regency period 2011-2012. The research had analytic observational study with case control approach around work area Pengaron Health Center, Sambung Makmur Health Center, Astambul Health Center, Pasayangan Health Center, and Dalam Pagar Health Center in Banjar Regency on May until September 2013. The sampling technique used was purposive sampling. The research sample were 30 maternal pregnant who have stillbirth incident (case) and 30 maternal pregnant who have livebirth (control) and suitable with inclusion criteria. The resource of research is conducted by secondary data. The data is analyzed by using Fischer exact and Chi Square. The results indicates that maternal pregnant of case had maternal height <145 cmis6,67%, increased weight gain during pregnancy <10 kg is 96,67%, maternal hemoglobin concentration <11 gr/dl is 76,67%, and maternal MUAC <23,5 cm is 50%. The conclusion with Fischer exact test: no correlation maternal height (p=0,671) and increased weight gain during pregnancy (p=0,195)with stillbirth incident. The conclusion with Chi Square test: there were correlation maternal hemoglobin concentration (p=0,001, OR=7,67)and maternal MUAC (p=0,001, OR=14)with stillbirth incident. Key words: nutritional status ofmaternal pregnant, maternal height, increased weight gain during pregnancy, maternal hemoglobin concentration, maternal MUAC, and stillbirth.